Melodi Produktivitas: Evaluasi Kesuksesan Aplikasi Spotify pada Kalangan Profesional Kota Jambi Berdasarkan Model Delone dan McLean - Fikri, M. Haikal; Jatriyono, Jatriyono; Kasrizal, Kasrizal (Universitas Batanghari Jambi, 2024)
Advancements in information technology have transformed the way society enjoys entertainment, including music. One of the leading platforms, Spotify, offers access to millions of songs that can be enjoyed anytime and anywhere. Using the Delone and McLean Model, this research aims to evaluate the success of Spotify usage among professionals in Jambi City. This model has six main dimensions: system, information, service, use, user satisfaction, and net impact. Data were collected through an online survey with 76 participants. The results indicate that system quality, information quality, and service quality positively influence user satisfaction and application usage. This research also emphasizes the importance of user characteristics in determining the success of Spotify usage. The findings provide insights for music application developers to enhance service quality and for professionals in Jambi City to leverage music as a tool to improve work productivity.